A Novel Homozygous Mutation Destabilizes IKKβ and Leads to Human Combined Immunodeficiency - Qin, Tao; Jia, Yanjun; Liu, Yuhang; Dai, Rongxin; Zhou, Lina; Okada, Satoshi; Tsumura, Miyuki; Ohnishi, Hidenori; Kato, Zenichiro; Kanegane, Hirokazu; Sun, Xiulian; Zhao, Xiaodong (Frontiers in Immunology, 2021)
Mutations in the IKBKB gene cause severe immunodeficiency, characterized clinically by persistent respiratory or gastrointestinal infections. Targeted gene panel sequencing revealed a novel homozygous missense mutation in the IKBKB gene of a patient with immune dysregulation and combined T and B cell functional defects. PBMCs from the patient, Ikbkb Y397H mice, and transfected cells were used to elucidate how the Y395H mutation triggers IKKβ deficiency and impairs immune function. Here, we found that cells from both the patient and Ikbkb Y397H mice lacked or showed decreased levels of IKKβ protein, along with impaired lymphocyte function. IKKα and IKKγ protein expression by human PBMCs harboring the Y395H mutation was normal, but degradation of IKKβ protein was accelerated. Binding of human NF-κB to DNA in patient PBMCs fell upon stimulation with TNF-α or LPS. Additionally, a structural model of Y395H revealed loss of the hydrogen bond with D389. These data suggest that IKBKB deficiency induces abnormal IKKβ protein degradation, leading to impaired NF-κB signaling and immune function. We postulate that the Y395H variant in the IKKβ protein lost the hydrogen bond with D389, thereby affecting interaction between Y395 and D389 and increasing protein instability.